(3OQI GdZhGU aj eMGVQI GdNhGUs - (3EHQGgje Hf Ydj Hf eMeO, GHf aQMhf, HQgGf GdOjf GdjYeQj J (B799 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi hSY cd TF QMeI hYdekG , hCSHZ Ydi GdNdGFb fYekG haVdkG LeG hHYO aEf WdH GdYde CTQa GdEcJSGH , hCSei , hWGdH jMJGL bhi hYRekG hSejJg hQJHJg Ydi CHhGH s
(3BNQgG (B:s
(3HGH GdaQGFV (B: (3aEf bdJ (B: (3EeQCI cJHJ dRhLgG GdZGFH Cf bO hVYJ hdOkG jQKc hdG JQKI hdjS HhdOc , hdG RfjJ Hg s
(3GdfSNI HgG MhGTs
(3cJHJ YfGhjf GdCHhGH hHYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3abg (B1367) s
Keywords: (3Gdabg GdESdGejs